SUSTAINABLE INNOVATIONS IN MSMES DURING THE ERA OF DIGITAL TRANSFORMATION: A STUDY IN INDONESIA - Sari, Mita Puspita; Sarumpaet, Tetty Lasniroha (Universitas Prof. Dr. Moestopo (Beragama), 2025)
Business value generation processes have been significantly impacted by digital transformation, especially for the Micro, Small, and Medium Enterprises (MSMEs) sector, which accounts for 61% of GDP and is the backbone of the Indonesian economy. This study is to review the most recent research on how MSMEs employ digitalization to address a range of opportunities and challenges in order to promote sustainable innovation in a changing global context. This study investigates the use of digital technology in MSMEs prior to, during, and following the Covid-19 pandemic using a combination of approaches. Sales turnover records were used to collect quantitative data, and in-person interviews with respondents were used to gather qualitative data. According to the analysis's findings, digital technology plays a significant role in enhancing MSME capacity to meet strategic objectives, which the COVID-19 epidemic has expedited. With the pandemic speeding up digital transformation and changes in consumer behavior toward digital transaction patterns leading to higher turnover, it was determined that digital technology is a significant catalyst for sustainable MSME growth. However, to overcome the different challenges MSMEs encounter, effective digitization necessitates deliberate policy backing and pertinent training initiatives.